Intersubjectivity and Temporality In the Choral Performance: A study about temporal information sources for choristers - Ordás, Manuel Alejandro (2012)
This research aims at examining choral performance as an embodied, intersubjective, and temporally organized practice of meaning. Choral research tradition focused mainly on the role of the conductor as determinant of the performance. Choral practice, however, would be the result of the entrained activity that occurs within the choir, also involving participants other than the choir conductor; it follows from this assumption that the way choir participants perform their individual and/or synchronized actions may affect the performance of the choir as a whole. The present proposal intends to carry out such examination: it aims at (i) investigating the nature of the temporal interaction among participants in the choir; and (ii) analyzing the temporal information sources that make viable such interaction. The study will focus on the interactions that occur between the choral conductor and the singers, and between the singers themselves as intentional agents that contribute to the make-up of choral perfomance. To begin with the study proposed, it has been developed a theoretical model to approach a preliminar analysis of the relationships that take place in the context of choral performance; it covers multiple relations of synchrony between singers-conductor (audiovisual) and singer-singer (auditory) that account for the complexity of the temporal phases that are present in choral performance. In the stage that follows, experimental testing is expected to be run with the purpose of i) identifing which attributes of the performance can be clues that performers use to interact with other performers, and ii) analyzing the influence of those attributes in the temporal coordination of singers and conductor. It is expected that the experimental use of some of the new and detailed analysis of sound and motion capture techniques (i.e. Optitrack infrared motion capture system among others), contributes to collect and analyse the empirical data, helping in the identification of those sources of visual, auditory or audiovisual temporal information that are most significant to match the accomplishment of singers and conductor during the choral performance.